Clinical Profile of Ankylosing Spondylitis and Outcome of Patients Treated with Infliximab - Dipankar Pal; Tusar Kanti Saradar; Dipanjan Halder; Kallol Paul; Sucheta Mandi; Pankaj Kumar Halder (Journal of Nature and Science of Medicine)
Introduction: Ankylosing spondylitis (AS) is a chronic inflammatory arthritis involving predominantly axial, and to a lesser extent, appendicular large joints, leading to bony ankylosis and fixed deformity. Anti-tumor necrosis factor therapy is the mainstay of treatment for AS. The present study was undertaken to document the efficacy and tolerability of infliximab in patients with AS in the regional population. Materials and Methods: In this prospective, observational, and longitudinal study, 36 patients with AS (Modified New York criteria) and Bath Ankylosing Spondylitis Disease Activity Index >4 without any significant comorbidity or contraindications to biologic therapy were included. All patients received infliximab and were followed for 48 weeks. Two patients were excluded during the follow-up due to death and adverse drug reactions (ADRs). Results: Out of 36 patients, 34 completed the study with a full course of infliximab without significant ADR. The male-to-female ratio of the study population was 11:1; the mean age was 23.91 years. Appendicular large joint involvement was noted in 47% of participants. Improvements in disease activity >50%, 25%–50%, and <25% were noted in 85%, 15%, and 0% of participants, respectively, at 48 weeks of follow-up. No relapse was noted during the study. Minor ADR not requiring withdrawal of therapy was noted in 25% of participants. Major ADR was seen in two (5%) patients. Conclusions: Infliximab therapy was effective and well tolerated in this regional study population.